Cost-Effectiveness Analysis of Power Generation in Turkish Republic of Northern Cyprus - Avcıoğlu, Yusuf (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Electrical energy has reached an indispensable position in production, transportation, distribution, and communication activities in the general economy. It is essential to human life with its prevalent use from lighting to heating, televisions to computers. With this feature, electrical energy rapidly replaces other forms of energy in proportion to the development level of countries. The situation is not different in the Turkish Republic of Northern Cyprus. With the increasing population and developing technology, the demand for electrical energy is increasing day by day. With the increase in demand, the installed power of the power plant is becoming more and more insufficient. This study analyzes the electrical energy supply sources "Fuel Oil, Natural Gas, and Interconnector," which can be used in the TRNC to meet the increasing energy demand. Cost-Effectiveness Analysis (CEA) and Levelized Cost Of Electricity (LCOE) production compare the most appropriate electricity supply to the country's conditions. It aims to identify the source of production.

ÖZ: Elektrik enerjisi aydınlatmadan ısıtmaya, televizyonlardan bilgisayarlara kadar son derece yaygın kullanım alanı ile insan hayatının vazgeçilmezi olduğu kadar genel ekonomi içinde üretim, ulaşım, dağıtım, iletişim faaliyetleri açısından da vazgeçilmez bir konuma ulaşmıştır. Bu özelliği ile elektrik enerjisi, ülkelerin gelişmişlik düzeyleri ile orantılı olarak hızla diğer enerji biçimlerinin yerini almaktadır. Kuzey Kıbrıs Türk Cumhuriyeti'nde de durum farklı değildir. Artan nüfus ve gelişen teknoloji ile birlikte elektrik enerjisine olan talep her geçen gün artmakta, talep artışı ile birlikte de kurulu santral gücü git gide yetersiz kalmaktadır. Bu çalışma, artan enerji talebini karşılamak amacıyla KKTC’de kullanılabilecek elektrik enerjisi tedarik kaynaları olan “Fuel Oil, Doğalgaz ve Enterkonnekte” ile elektrik üretiminin Maliyet Etkililik Analizini (CEA) ve Seviyelendirilmiş Elektrik Maliyetini (LCOE) karşılaştırmalı olarak analiz ederek, ülke şartlarına en uygun üretim kaynağını belirlemeyi amaçlamaktadır.
Master of Science in Energy Economics and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2021. Co-Supervisor: Assoc. Prof. Dr. Hasan Ulaş Altıok and Supervisor: Prof. Dr. Glenn Paul Jenkins.
Keywords: Thesis Tez; Economics Department; Energy Economics and Finance; Power--Energy--Power Generations--Economics--Cyprus (Turkish Republic of Northern Cyprus, 1983-).; Steam power plants; Electric power systems; Energy Production--Economics--Thermal Power Generation--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Electricity Production--Electricity Generations--Economics; TRNC; Electricity generation; CEA; LCOE; HFO; CCGT; LNG